2014
DOI: 10.1039/c3dt52447g
|View full text |Cite
|
Sign up to set email alerts
|

Co-precipitation synthesis of nanostructured Cu3SbSe4and its Sn-doped sample with high thermoelectric performance

Abstract: Large-scale fabrication of nanostructured Cu3SbSe4 and its Sn-doped sample Cu3Sb0.98Sn0.02Se4 through a low-temperature co-precipitation route is reported. The effects of hot-pressing temperatures, time and Sn doping on the thermoelectric properties of Cu3SbSe4 are explored. The maximum figure of merit ZTmax obtained here reaches 0.62 for the un-doped Cu3SbSe4, which is three times as large as that of Cu3SbSe4 synthesized by the fusion method. Due to the ameliorated power factor by optimized carrier concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 22 publications
4
36
1
Order By: Relevance
“…7 shows the carrier density dependence of the Seebeck coefficient and Hall mobility at room temperature, together with the data previously reported for this system. 23,33,42 We found that the SPB model with acoustic phonon scattering assumption could well explain both properties. From the carrier density dependence of the Seebeck coefficient (the Pisarenko relation), it seems that all the measured S are consistent with a constant density-of-state (DOS) effective mass, m* ¼ 1.5 m e .…”
Section: Resultsmentioning
confidence: 83%
“…7 shows the carrier density dependence of the Seebeck coefficient and Hall mobility at room temperature, together with the data previously reported for this system. 23,33,42 We found that the SPB model with acoustic phonon scattering assumption could well explain both properties. From the carrier density dependence of the Seebeck coefficient (the Pisarenko relation), it seems that all the measured S are consistent with a constant density-of-state (DOS) effective mass, m* ¼ 1.5 m e .…”
Section: Resultsmentioning
confidence: 83%
“…The finite-temperature structural characteristics of Cu 3 SbSe 3 , a new type of TE material, could further demonstrate the deviation from the static and small-vibration picture. Cu-Sb-Se systems have been shown to possess a ZT value about unity (31,32), and Cu 3 SbSe 3 manifests anomalously low lattice thermal conductivity (0.7-1.0 Wm -1 ·K −1 ) with an unusual temperature dependence (33, 34) (see An Effective Approach for the Thermal Transport in Part-Crystalline Part-Liquid Materials) and has also been expected to possess a ZT value about unity (35). In the compound, certain type of constituent atoms weakly bond to the rest of lattice with relatively strong rigidity.…”
Section: Resultsmentioning
confidence: 99%
“…Few reports have also detailed the production of bulk nanostructured CASe. [32][33][34] However bottom-up strategies to cost-effectively produce efficient CASe NCs, nanomaterials and CASe-based devices remain to be demonstrated. Here, we report a solution-based scalable synthesis approach to produce several grams of monodisperse CASe NCs doped with controlled amounts of Sn and Bi.…”
Section: Introductionmentioning
confidence: 99%